PENGARUH PROBLEM BASED INSTRUCTION (PBI) BERBANTUAN GENIALLY TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATERI PELUANG - Indarmas; Widiawati; Helni Indrayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low problem-solving ability of students in opportunity materials based on previous research. This study aims to determine the influence of Genially-assisted Problem Based Instruction (PBI) on the problem-solving ability of grade VIII students at SMP Negeri 1 Tanjung Sakti Pumu. This study uses a quantitative approach with an experimental method. The research sample amounted to 48 students who were selected using random sampling techniques consisting of two classes, namely the experimental class that used Genially-assisted Problem Based Instruction (PBI) learning and the control class that used conventional learning methods. The research instruments are in the form of pretest and posttest tests. The results showed that there was a significant increase in students' problem-solving ability in the experimental class reaching 68.08%, higher than the control class of 55.45%. As well as the results of statistical tests that show a significant influence. These results prove that the application of Problem Based Instruction (PBI) learning assisted by Genially is effective in improving students' problem-solving skills.